Requirements-driven and multi-homed-based multipath TCP congestion control algorithm for vehicular network - Nan DING; Tao LIN; Cai-xia SONG; Guo-zhen TAN (Tongxin xuebao)
To meet the diversified QoS applications demanded by terminal units of a VANET, especially to ensure the timeliness and reliability when sending the high-priority messages that were related to safety-critical applications, a de-mand-driven MPTCP congestion control algorithm: PTLIA was proposed, which was based on message priority and throughput estimation. First, message priority and throughput proportion factor were defined to characterize the weight of each message being sent. Second, the patch estimation model was used to make real-time estimation of the state of each MPTCP path. Finally, the algorithm of PTLIA was accordingly designed to adjust, dynamically, the window of the con-gestion time on demand. The algorithm of PTLIA, as proved in proposed simulations and experiments, has shortened the transmission of the high-priority data, under the premise of MPTCP transmission principles.